ANALYSIS OF THE SUPPLY AND DISTRIBUTION OF ISLAMIC PUBLIC ASSETS FROM A SPIRITUAL MANAGEMENT PERSPECTIVE - Atmaja, Diyaa Aaisyah Salmaa Putri; Purbawati, Purbawati; Rosanti, Ida (Journal of Sustainable Transformation, 2023)
This research intends to uncover, explain and analyze the concept of Islamic thought from Sheikh Taqiyuddin an-Nabhani regarding the provision and distribution of public finances in Baitul Maal by taking the perspective of heavenly management. The research results reveal that Sheikh Taqiyuddin An-Nabhani's concept of supply and distribution management of public finances in Baitul Maal is essentially a revenue and expenditure concept that reflects the income and expenditure allocation of the caliphate state in accordance with the principles of Islamic religious law. General analysis shows that the concept of Baitul Maal in the thoughts of Sheikh Taqiyuudin An-Nabhani explains that Baitul Maal manages community assets on a state scale and emphasizes the role of Islamic political riayah 'ala syu'unil ummat (management of the affairs of the people) by dawlah and imam/caliph. Meanwhile, formal object analysis shows that the concept of Baitul Maal in the thoughts of Sheikh Taqiyuddin An-Nabhani contains values that fulfill the realm of Life is Place of Wealth as a domain in celestial/spiritual management.